Impact of InsurTech in Reducing the Out-of-Pocket Expenses (OOPE) in Indian Healthcare - Kumar, Venkatraman (Digital Repository of Theses, 2025)
Out-Of-Pocket-Expenses (OOPE) in healthcare refers to the costs that individual must pay directly for medical services or treatments either due to no insurance coverage or due to policy exclusion / rejection by the Health Insurance company. In India, OOPE is known to be the topmost in the world-wide; Low health Insurance penetration, high claim rejection and insufficient cover are top points for high out of income health expenses. InsurTech in Healthcare refers to the use of Digital Transformation across Payer operations, Provider operations & Member interactions to improve health insurance awareness, enhance member experience & reduce cost. The current gap in the existing literature is there is no drilldown to identify the critical factors that has high impact on Out-Of-Pocket-Expenses (OOPE) and how InsurTech can help address those factors. Through this study I would like to identify the critical factors responsible for Out-Of-Pocket Expenses & highlight how InsurTech can help bridge the gap between each stakeholder in the Indian healthcare value chain - Health Insurance Payer, Healthcare Provider & Members to create an ecosystem that can minimize the Out-Of-Pocket Expenses.